Current Approaches and Future Directions for the Treatment of mTORopathies - Karalis, Vasiliki; Bateup, Helen S. (Developmental neuroscience, 2021)
The mechanistic target of rapamycin (mTOR) is a kinase at the center of an evolutionarily conserved signaling pathway that orchestrates cell growth and metabolism. mTOR responds to an array of intra- and extracellular stimuli and in turn controls multiple cellular anabolic and catabolic processes. Aberrant mTOR activity is associated with numerous diseases, with particularly profound impact on the nervous system. mTOR is found in two protein complexes, mTOR complex 1 (mTORC1) and 2 (mTORC2), which are governed by different upstream regulators and have distinct cellular actions. Mutations in genes encoding for mTOR regulators result in a collection of neurodevelopmental disorders known as mTORopathies. While these disorders can affect multiple organs, neuropsychiatric conditions such as epilepsy, intellectual disability, and autism spectrum disorder have a major impact on quality of life. The neuropsychiatric aspects of mTORopathies have been particularly challenging to treat in a clinical setting. Current therapeutic approaches center on rapamycin and its analogs, drugs that are administered systemically to inhibit mTOR activity. While these drugs show some clinical efficacy, adverse side effects, incomplete suppression of mTOR targets, and lack of specificity for mTORC1 or mTORC2 may limit their utility. An increased understanding of the neurobiology of mTOR and the underlying molecular, cellular, and circuit mechanisms of mTOR-related disorders will facilitate the development of improved therapeutics. Animal models of mTORopathies have helped unravel the consequences of mTOR pathway mutations in specific brain cell types and developmental stages, revealing an array of disease-related phenotypes. In this review, we discuss current progress and potential future directions for the therapeutic treatment of mTORopathies with a focus on findings from genetic mouse models.